Blue laser welding of low thickness Ni-coated copper and mild steel for electric vehicle (EV) battery manufacturing. (November 2022) - Sadeghian, Amirhossein; Iqbal, Naveed
Highlights: The applicability of a blue laser system for welding Ni-coated copper and mild steel. Blue laser welding of cylindrical cell terminals for the first time. Effects of process parameters on microstructure and mechanical properties. Effect of corrosive environment on joint strength. Abstract: Modern advancements in blue lasers offer a promising alternative to conventional infrared laser welding of highly-reflective battery materials. In this study, a high-power blue laser system was used to weld the low thickness Ni-coated copper and mild steel used in 18650-type cylindrical cells. The effect of laser power on the penetration depth, interface width, and weld bead quality was studied. The weld microstructure was characterized by employing optical microscopy, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The mechanical performance of the welds was evaluated through peel testing and microhardness measurements. The results show that the penetration depth and weld width increased with laser power. Increasing the laser power to more than 1.3 kW resulted in a damaging effect on weld bead quality creating defects such as crack, under-fill, and distortion due to excessive heat input. Weld samples fractured in the heat-affected zone of Ni-coated copper during peel testing due to grain growth in copper. The maximum peel strength of 158.8 N was achieved for the 1.2 kW sample. The formation of a composite microstructure between Cu and Fe with a higher hardness than parent metals was observed inside the weld nugget. The hardness of this zone increased with the laser power due to an increase in the amount of Fe, reaching 185 HK for the 1.5 kW sample. By exposure to a corrosive environment, the peel strength drastically decreased and the failure occurred at the weld interface. For the 1.2 kW sample, the peel strength was reduced to around 57 N. The process initially developed for coupons of Ni-coated copper and mild steel was further tested on the positive and negative tabs of 18650-type cylindrical cells. The weld microstructure showed a lack of defects. However, due to varying thicknesses and associated heat sinks further process refinement is required for optimum joint quality.